Chitin metabolism in insects: chitin synthases and beta-N-acetylglucosaminidases - Hogenkamp, David George (Kansas State University, 2006)
Chitin, a linear homopolymer of beta-1,4-linked N-acetylglucosamine, is the second most abundant biopolymer next to cellulose. It is the major structural polysaccharide in the insect’s exoskeleton and gut lining. An extensive study of two of the major genes encoding enzymes involved in chitin metabolism, chitin synthases (CHSs) and beta-N-acetylglucosaminidases (NAGs), was undertaken. CHS genes from the tobacco hornworm, Manduca sexta, and NAG genes from the red flour beetle, Tribolium castaneum, were identified and characterized. In general, chitin deposition occurs in two major extracellular structures of insects, the cuticle that overlays the epidermis, and the peritrophic membrane (PM) that lines the midgut. Only two CHS genes were identified in M. sexta using Southern blot analysis. Extensive expression studies of both M. sexta CHS genes, MsCHS1 and MsCHS2, suggest a strict functional specialization of these two genes for the synthesis of epidermal and PM-associated chitin, respectively. Furthermore, two alternatively spliced transcripts of MsCHS1, MsCHS1a and MsCHS1b, were identified. Analysis of the levels of these transcripts in different tissues and stages of development indicated that the MsCHS1a transcript predominates in the integument during the feeding and pupal stages, whereas the MsCHS1b transcript is more abundantly present in the tracheae, foregut, and hindgut during all developmental stages tested. Four genes encoding putative NAGs (TcNAG1, TcNAG2, TcNAG3, and TcNAG4) were identified by searching the Tribolium genomic database. The full-length cDNAs for all four NAGs were cloned and sequenced, and the exon-intron organizations were determined. Studies on developmental expression patterns of each gene indicated that they are expressed during most developmental stages with TcNAG1 being the predominant one. The function of each NAG was assessed by down regulating the level of each transcript at various developmental stages using RNA interference. Selective knock down of each transcript, without significant reduction in the expression levels of the other NAG transcripts, was verified and the resulting phenotypes were documented. Knockdown of TcNAG1 interrupted larval-larval, larval-pupal, and pupal-adult molting, and the insects were unable to completely shed their old cuticles.
Keywords: Chitin synthase; N-Acetylglucosaminidase; Manduca sexta; Tribolium castaneum; Cuticle; Midgut; Biology, Entomology (0353); Biology, Molecular (0307); Chemistry, Biochemistry (0487)